Enhancing Employee Productivity Through Effective Occupational Health and Safety Practices - Edwar, Rizka Cintya; Damanik, Lisa Gresti Sella; Harju, Leon Mitra; Toii, Indra Eka Wardana; Mangopo, Yuni Riskita (Jurnal Manajemen Dan Akuntansi Medan, 2025)
Background: Occupational health and safety (OHS) programs are essential for ensuring the well-being of employees, particularly in sectors with high-risk environments such as the energy industry. Despite the existence of OHS programs, the effectiveness of these programs in enhancing employee productivity remains underexplored in certain regions. This research focuses on PT PLN UP3 Sorong, a state-owned company in Indonesia, to examine the impact of OHS on employee productivity. Research Objective: The purpose of this study is to analyze the effect of OHS on employee work productivity at PT PLN UP3 Sorong. Research Method: This quantitative study employs a descriptive causal design to examine the relationship between OHS and work productivity. The data were collected from 35 employees of PT PLN UP3 Sorong through questionnaires. Data analysis was conducted using simple linear regression with the help of SPSS software. Results: The findings reveal that OHS has a significant and positive effect on employee productivity. The results indicate that improvements in OHS practices lead to an increase in work productivity among employees. The statistical analysis shows that the implementation of OHS is crucial in boosting employee performance, and the correlation between the variables is strong. Conclusion: The study concludes that OHS significantly contributes to enhancing employee productivity at PT PLN UP3 Sorong. The findings emphasize the importance of investing in OHS programs to improve employee well-being and organizational performance. Companies, especially state-owned enterprises, should prioritize these programs for sustained productivity.